The necessity of educating small-scale farmers on Agritourism adoption: A recipe for economic development in Zimbabwe. - Chinongwa, Edward; Nemashakwe, Paul; Chiriseri, Esther (Universitas Kuningan, 2024)
The agriculture industry is experiencing tremendous challenges across the globe due to various factors. These factors include globalisation, falling commodity prices, free-trade promotions, oversupply of goods and services, changes in subsidy policies, environmental changes, climate change, low-income elasticities in commodity markets, and over-reliance on raw products. This has resulted in the hopelessness of the agriculture industry leaving farmers seeking to explore the viability of alternative economic strategies in an effort to preserve and maintain the productivity of their family lands. Zimbabwe as an agro-based economy, with agriculture contributing substantially to the country’s Gross Domestic Product (GDP), is not spared by the scourge. Irrespective of the different challenges bedeviling farmers, they still need to remain viable. One key strategy that will be a panacea to this quagmire is the amalgamation of agriculture and tourism sectors under the concept of agritourism. This paper is a conceptual discussion that argues for the education of farmers on the concept of agritourism and its benefits. This is critical and necessary for economic development in Zimbabwe. The discussion positions education as an important ingredient for the adoption and success of agritourism. All the countries that are currently benefiting from agritourism use education as a way of imparting skills, knowledge and improving attitudes and perceptions among farmers.Keywords: agritourism; economic development; education; small-scale farmers.